Amelanotic naevoid melanoma in a 16‐month‐old albino infant. (2nd December 2016) - Knöpfel, N.; Martín‐Santiago, A.; Del Pozo, L. J.; Saus, C.; Pascual, M.; Requena, L.
Summary: Melanoma in individuals with oculocutaneous albinism has been reported in the literature to be rare compared with the more common occurrence of squamous cell carcinoma and basal cell carcinoma. We present a singular case of amelanotic naevoid melanoma arising from a small congenital naevus in a 16‐month old albino boy, the youngest reported to date.